Evaluation of the Effect of Nd:YAG and CO2 Laser Dentin Treatment Techniques on Shear Bond Strength of Composite Resin - Sharafeddin , Farahnaz; Torabi Parizi, Arefeh; Jamshidi, Maryam (Galen Medical Journal, 2025)
Background: Recently, lasers have been used for composite resin adhesion, yielding conflicting results. The shear bond strength (SBS) of resin composites to dentin when lasers are used as an alternative to acid etching or in conjunction with acid etching remains unclear. This study aimed to investigate the effect of Nd:YAG and CO2 laser as treatment techniques on composite resin bond strength. Materials and Methods: Seventy teeth were divided into seven groups: G1 (control) received 37% phosphoric acid etching, G2 was treated with a CO2 laser, G3 with an Nd: YAG laser, G4 with a combination of CO2 and Nd: YAG lasers, G5 underwent CO2 laser treatment after acid etching, G6 received Nd: YAG laser treatment after acid etching, and G7 underwent a combination of CO2 and Nd: YAG lasers after acid etching. Adper Single Bond 2 was used. SBS was determined after thermocycling and statistically analyzed using the Kruskal-Wallis test. Specimens were examined for fracture types under a stereomicroscope at 40X magnification. Results: Control group had highest SBS (11.14±1.97 MPa, p≤0.004 vs all). Acid+Nd:YAG (8.19±3.13 MPa) showed better bonding than CO₂ (2.07±1.38, p=0.001), Nd:YAG (3.11±2.11, p=0.002), and Acid+CO₂ (2.38±1.52, p=0.001). Adhesive failures dominated (73%); no cohesive failures occurred. Acid+Nd:YAG performed best among surface treatments. Conclusion: The SBS decreased following the application of CO2 and Nd: YAG lasers, either alone or in combination. However, after the application of phosphoric acid, lasers yielded improved results, although they remained lower than the control group.